Comprehensive Analysis of Familial Parkinsonism Genes in Rapid‐Eye‐Movement Sleep Behavior Disorder. Issue 1 (1st October 2020) - Mufti, Kheireddin; Rudakou, Uladzislau; Yu, Eric; Krohn, Lynne; Ruskey, Jennifer A.; Asayesh, Farnaz; Laurent, Sandra B.; Spiegelman, Dan; Arnulf, Isabelle; Hu, Michele T.M.; Montplaisir, Jacques Y.; Gagnon, Jean‐François; et al.
ABSTRACT: Background: There is only partial overlap in the genetic background of isolated rapid‐eye‐movement sleep behavior disorder (iRBD) and Parkinson's disease (PD). Objective: To examine the role of autosomal dominant and recessive PD or atypical parkinsonism genes in the risk of iRBD. Methods: Ten genes, comprising the recessive genes PRKN, DJ‐1 (PARK7), PINK1, VPS13C, ATP13A2, FBXO7, and PLA2G6 and the dominant genes LRRK2, GCH1, and VPS35, were fully sequenced in 1039 iRBD patients and 1852 controls of European ancestry, followed by association tests. Results: We found no association between rare heterozygous variants in the tested genes and risk of iRBD. Several homozygous and compound heterozygous carriers were identified, yet there was no overrepresentation in iRBD patients versus controls. Conclusion: Our results do not support a major role for variants in these genes in the risk of iRBD. © 2020 International Parkinson and Movement Disorder Society